Characterisation and functional analysis of canine TLR5. Issue 6 (August 2020) - Zhu, Aihua; Wei, Lingling; Hu, Sujuan; Yang, Cheng; Chen, Caifa; Zhou, Zhengkun; Pan, Zhiming
In this study, we characterised the single exon TLR5 gene of the Chinese rural dog. Sequence analysis revealed a 2577 nucleotide-long open reading frame of canine TLR5, encoding an 858 amino acid-long protein. The putative amino acid sequence of canine TLR5 consisted of a signal peptide sequence, 15 LRR domains, a LRR C-terminal domain, a transmembrane domain and an intracellular Toll-IL-1 receptor domain. The amino acid sequence of the canine TLR5 protein shared 95.4% identity with vulpine, 72.2% with feline and 64.7% with human TLR5. Plasmids expressing canine TLR5 and NF-κB-luciferase were constructed and transfected into HEK293T cells. Expression was confirmed by indirect immunofluorescence assay. These HEK293T cells transfected with the canine TLR5- and NF-κB-luciferase plasmids signiﬁcantly responded to ﬂagellin from Salmonella enteritidis serovar Typhimurium, indicating that it is a functional TLR5 homolog. In response to stimulation with Salmonella enteritidis, the level of TLR5 mRNA significantly increased over the control in PBMCs at 4 h. The levels of IL-8, IL-6 and IL-1β also increased after exposure. The highest levels of TLR5, IL-8 and IL-1β expression were detected at 8, 4 and 12 h after stimulation, respectively. These results imply that the expression of canine TLR5 may participate in the immune response against bacterial pathogens.